The association between dental health locus of control and sociodemographic factors among urban and rural people in Davangere, India - Pranati Eswar; C G Devaraj (Wolters Kluwer Medknow Publications, 2015)
Introduction:Oral diseases have underlying socio-behavioral determinants. Oral health promotion programs aimed at behavior modification will be effective if the factors that motivate health behaviors are known. One of the constructs widely used to predict and analyze health behaviors is the health locus of control scale (HLOC). Aim: To determine the association between sociodemographic factors and dental HLOC among a selected sample of urban and rural people in Davangere district, Karnataka state, India. Materials and Methods: The study sample consisted of 300 people, 150 each from urban and rural area, aged 18 years and above. Sociodemographic data was collected by a self-administered questionnaire. Dental HLOC was assessed by a questionnaire prepared by the author in local language. The association between sociodemographic variables and dental HLOC was analyzed using Chi-square test. Results: Significantly more number of people in urban area had internal LOC when compared to rural people (P = 0.00). There was significant association between gender in rural areas (P < 0.001), education level (P < 0.001) and socioeconomic status (P < 0.001) with dental HLOC. There was no significant association between age, gender in urban areas and marital status with dental HLOC. Conclusions: Gender, education level and socioeconomic status were associated with dental HLOC beliefs. The findings can be useful in planning effective oral health promotion programs aimed at positive oral health behavior modification for people from varying sociodemographic backgrounds by modifying their health control beliefs.